KERUSAKAN TEGAKAN TINGGAL PADA TEKNIK REDUCED IMPACT LOGGING DI INDONESIA: TINJAUAN SISTEMATIS - Ahmad budiaman; Nazma Rahayu (Forestry Study Program University Of Mataram, 2023)
Forest harvesting in the natural production forest management in Indonesia is mostly carried out using conventional logging techniques and causes serious damage to residual stands and soil resources. One of the efforts made to reduce this environmental damage is the application of reduced impact logging (RIL) techniques. This study aimed to collect and analyze research results related to the damage to residual stands caused by RIL in the natural production forest management in Indonesia. This study used a systematic review method. A systematic literature search was carried out at data sources such as Google Scholar, Research Gate, Science Direct, and SINTA, which were published between 1996-2021. All studies reported that applying RIL techniques can reduce the damage to the residual stands.